The Impact of Attitude, Subjective Norm and Information Communications Technology on Knowledge Sharing among Academic Staff - S. Mousa, Talal; S. JAMEEL, Alaa; Ahmad, Abd Rahman (International Journal of Psychosocial Rehabilitation, 2019)
Knowledge sharing (KS) is essential to institutional success. However, knowledge sharing within organizations would greatly affect their efficiency, as it stimulates the ability of people to tackle problems within the organization. Meanwhile, limited studies have been conducted in the Iraqi context to find the impact on KS among academic staff. The purpose of this study is to investigate and examine the impact of attitude, subjective norm, and information and communication technology on KS among academic staff in an Iraqi context. Methodology: The study was conducted at Al-Anbar University among academic staff. 152 valid questioners have been analyzed by structural equation modeling (AMOS). The questioners consisted of four main variables, namely: attitude, subjective norm, and information and communications technology as independent variables, while the dependent variable is KS. Main Findings indicated that all three variables have a positive and significant impact on KS among academics’ staff. It is necessary for higher education as a whole to have academics with the feeling of sharing their expertise without withholding any element or component owing to self-interest. Originality/Novelty: This research helps to enrich the body of knowledge in Middle Eastern nations, especially in Iraq and higher education, by examining the influence of knowledge sharing.